2002
DOI: 10.1161/01.cir.0000033830.36431.46
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Id1 Expression by Bone Morphogenetic Protein Is Sufficient and Necessary for Bone Morphogenetic Protein–Induced Activation of Endothelial Cells

Abstract: The BMP/Smad pathway can potently activate the endothelium. Id1 expression is strongly induced by BMP in ECs. Ectopic expression of Id1 induces EC migration and tube formation. Moreover, Id1 played a critical role in mediating BMP-induced EC migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
211
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(229 citation statements)
references
References 21 publications
15
211
3
Order By: Relevance
“…Up-regulation of ID genes is an important event in this response, and has been demonstrated to be dependent on Smad phosphorylation [8]. We used a reporter assay to demonstrate this also in Jurkat TAg cells.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Up-regulation of ID genes is an important event in this response, and has been demonstrated to be dependent on Smad phosphorylation [8]. We used a reporter assay to demonstrate this also in Jurkat TAg cells.…”
Section: Discussionmentioning
confidence: 91%
“…The dependency on Id1 up-regulation is in accordance with studies of BMP effects in other cellular systems. In endothelial cells it has been shown that BMP-6 stimulated migration and tube formation via Id1 up-regulation [8]. The functional effects of BMP-2 in a lung cancer cell line were also related to Smad1-dependent up-regulation of Id1 [6].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…At the same time, BMP6 significantly inhibits in vitro tubule formation by human endothelial cells down to the level of the negative control (Figure 4), giving a further possible link with BM angiogenesis and thus prognosis. These were surprising results, as BMP6 has been described as an agonist for endothelial cell migration and tube formation in vitro (Valdimarsdottir et al, 2002) using adenoviral-transfected BMP-receptor-expressing mouse embryonic endothelial cells and bovine aortic endothelial cells. Differences might be explained by speciesdependent action of BMP6 and/or receptor expression or a difference in action of BMP6 on embryonic vs adult endothelial cells.…”
Section: Biological Implicationsmentioning
confidence: 94%
“…In prostate (Hamdy et al, 1997;Haudenschild et al, 2004;Dai et al, 2005) and breast cancer (Clement et al, 1999), BMP6 expression promotes tumor progression and metastasis. BMP6 has been described to be a proangiogenic factor in terms of endothelial cell migration and tube formation in vitro (Valdimarsdottir et al, 2002).…”
Section: Introductionmentioning
confidence: 99%